2012
DOI: 10.1037/a0026480
|View full text |Cite
|
Sign up to set email alerts
|

Tuning in to Kids: An effectiveness trial of a parenting program targeting emotion socialization of preschoolers.

Abstract: This article reports on an effectiveness trial of the Tuning in to Kids (TIK) parenting program. TIK aims to improve emotion socialization practices in parents of preschool children; it is a universal prevention program that teaches parents the skills of emotion coaching and also targets parents' own emotion awareness and regulation. The present study followed a 2 ϫ 2 (Treatment Condition ϫ Time) design. One hundred twenty-eight parents of children ages 4.0 -5.11 years were recruited from preschools and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 38 publications
4
73
4
1
Order By: Relevance
“…Therefore, the findings from this study has significant implications for families as a whole, in terms of their roles and how they may influence children's brain anatomy as well as social and emotional development. As previous research has indicated, the types of meta-emotion approaches parents adopt may influence children's emotion regulation abilities and social competence skills (Lunkenheimer & Cortina, 2007;Wilson et al, 2012).…”
Section: Environmental Factors and Emotion Socializationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the findings from this study has significant implications for families as a whole, in terms of their roles and how they may influence children's brain anatomy as well as social and emotional development. As previous research has indicated, the types of meta-emotion approaches parents adopt may influence children's emotion regulation abilities and social competence skills (Lunkenheimer & Cortina, 2007;Wilson et al, 2012).…”
Section: Environmental Factors and Emotion Socializationmentioning
confidence: 99%
“…The types of meta-emotion approaches parents adopt are quite significant, as they have been found to be associated with children's socialization and emotion regulation abilities (Lunkenheimer & Cortina, 2007;Wilson et al, 2012). Children's abilities to regulate their emotions is associated with executive functions in their brains, which are also responsible for higher level thinking processes, such as attention, inhibitions of negative emotions, and memory (Graziano, Reavis, Keane, & Calkins, 2007).…”
Section: Significance Of Meta-emotion Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the emotional atmosphere is negative, the child can become reactive and emotionally insecure (Morris et al, 2007). Nevertheless, parental training for handling the emotions of the children has shown positive results (Wilson, Havighurst, & Harley, 2012), indicating that the influence of parents on the child's RE can be adjusted.…”
Section: Introductionmentioning
confidence: 99%